Hydraulic Press Machine Design for Straw Processing System: Desain Mesin Pres Hidraulik untuk Sistem Pengolahan Jerami - Muhammad Rizal Ma’arif; A’rasy Fahruddin (Indonesian Journal of Innovation Studies, 2025)
This study presents the design and development of a hydraulic-based pressing machine for material processing applications. General Background: Hydraulic systems are widely utilized in industrial machinery due to their ability to generate high force with controlled motion. Specific Background: In agricultural and mechanical sectors, pressing processes require efficient and reliable equipment to improve material handling and productivity. Knowledge Gap: Existing systems often lack optimization in terms of design simplicity, operational efficiency, and adaptability for small-scale applications. Aims: This research aims to design and analyze a hydraulic press machine capable of improving pressing performance for processing materials such as straw. Results: The developed system demonstrates stable mechanical performance, adequate pressure distribution, and operational feasibility under testing conditions. Novelty: The proposed design integrates a simplified hydraulic mechanism with practical implementation considerations suitable for small-scale usage. Implications: The findings provide a reference for developing cost-effective hydraulic machinery in agricultural and industrial applications, supporting improved productivity and equipment accessibility. Keywords: Hydraulic System, Press Machine, Mechanical Design, Straw Processing, Industrial Equipment Key Findings Highlights Hydraulic mechanism shows stable force generation during operation Prototype supports consistent material compaction process Design suitable for small-scale industrial implementation